Application of Free Water Surface Constructed Wetland for Reduction of Brantas River Pollutants - Popi Wahyuni Masriyanto; Anie Yulistyorini; Dian Ariestadi (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
Brantas River is a raw clean water sources that flow through Malang City. The Brantas River water is polluted due to discharging of untreated wastewater, causing a decrease in river water quality. According to these problems, exploring water resources through Brantas River water treatment is essential using Free Water Surface Constructed Wetland (FWSCW) which aims to analyze the performance and improve the water quality of the Brantas River using these wetlands. The research was conducted on a laboratory scale with control treatment and FWSCW with aquatic plants such as Pistia stratiotes, Echinodorus palaefolius, and Heliconia psittacorum. The results showed that pH and temperature were stable, with values between 7.63 to 8.53 and 23°C to 27°C. The removal efficiency of FWSCW and control in reducing turbidity was 99.53% and 98.55%, respectively, and TDS reduction was 0.56% and 2.84%, respectively, for control and FWSCW. The water quality has met the 2nd class of the water quality standards based on Government Regulation of the Republic of Indonesia No. 82 of 2001. At the same time, the efficiency of reducing BOD concentration was 89%. The results show that the FWSCW system can be used as a secondary treatment system to produce clean water.